2017
DOI: 10.1016/j.jcmgh.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Inhibition of Pancreatic Acinar Cell Calcineurin Is a Novel Strategy to Prevent Post-ERCP Pancreatitis

Abstract: Background and Aims There is a pressing need to develop effective preventative therapies for post-ERCP pancreatitis (PEP). We demonstrated that early PEP events are induced through the calcium-activated phosphatase calcineurin and that global calcineurin deletion abolishes PEP in mice. A crucial question is whether acinar cell calcineurin controls the initiation of PEP in vivo. Methods We used a mouse model of PEP and examined the effects of in vivo acinar cell-specific calcineurin deletion by either generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…We and others showed that healthy human acinar cells isolated from cadaveric tissue retain their morphology and functional characteristics, which has allowed examination of early pancreatitis responses to a number of stressors, e.g., bile salts. 72,98,100,113,126,127 We characterized physiologic and pathophysiologic responses of the human acinar cell preparations and found them similar to those observed in mouse ex-vivo models. 126 In particular, disordered organelle responses: the ER stress, aberrant Ca 2+ signal, mitochondrial depolarization, and impaired autophagy -are all prominent in ex-vivo pancreatitis on human acinar cells.…”
Section: Disordering Of Acinar Cell Organelles In Human Pancreatitismentioning
confidence: 84%
“…We and others showed that healthy human acinar cells isolated from cadaveric tissue retain their morphology and functional characteristics, which has allowed examination of early pancreatitis responses to a number of stressors, e.g., bile salts. 72,98,100,113,126,127 We characterized physiologic and pathophysiologic responses of the human acinar cell preparations and found them similar to those observed in mouse ex-vivo models. 126 In particular, disordered organelle responses: the ER stress, aberrant Ca 2+ signal, mitochondrial depolarization, and impaired autophagy -are all prominent in ex-vivo pancreatitis on human acinar cells.…”
Section: Disordering Of Acinar Cell Organelles In Human Pancreatitismentioning
confidence: 84%
“…ERCP was performed as previously described (17)(18)(19). Female Swiss Webster mice were used for these experiments, which were performed at the University of Pittsburgh.…”
Section: Eip and Fgf21 Treatmentmentioning
confidence: 99%
“…To this end, Orabi et al, 3 in this issue of Cellular and Molecular Gastroenterology and Hepatology , evaluated the role of calcineurin in an animal model of endoscopic retrograde cholangiopancreatography (ERCP)-induced pancreatitis. This group previously reported that pancreatitis produced by injection of either bile acids or radiocontrast into the pancreatic duct activated calcineurin and nuclear factor-κB and was ameliorated by pharmacologic calcineurin inhibition or global deletion of the calcineurin gene in mice 4 …”
mentioning
confidence: 99%
“…Was calcineurin in T cells or acinar cells important for pancreatitis? To address this question, Orabi et al 3 deleted the calcineurin gene specifically in acinar cells in conditional knockout mice or with an acinar cell–specific viral targeting vector. Their results showed that calcineurin in the pancreas mediated acute pancreatitis.…”
mentioning
confidence: 99%
See 1 more Smart Citation